2001
DOI: 10.1645/0022-3395(2001)087[0587:ciratt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Response and Th1/Th2 Cytokines in Human Neurocysticercosis: Lack of Immune Suppression

Abstract: Some reports have suggested that human neurocysticercosis (NCC) induces immunosuppression. To test this hypothesis, we performed a study on active cases of NCC who had not received cestocidal or immunosuppressive treatments. We examined blood counts and specific T cell markers (CD3, CD4, and CD8) by flow cytometry and found no differences between patients with NCC and healthy individuals. Both groups responded to concanavalin A (Con A), and patients with NCC responded more to a parasite crude antigen than unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Likewise, dendritic cells stimulated with helminth components show limited upregulation of CD80, CD86 and MHC-II expression in comparison to the expression induced by bacterial antigens [37]. In some studies has been shown that NCC patients exhibit a depressed peripheral cellular immune response [38], although this is controversial [39],[40]. In other helminth infections, results indicate that released products may interfere with the generation of pro-inflammatory mediators [41], the antigen presentation process [42] and other immune defense mechanisms elicited by the host upon helminth infection [3],[43],[44].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, dendritic cells stimulated with helminth components show limited upregulation of CD80, CD86 and MHC-II expression in comparison to the expression induced by bacterial antigens [37]. In some studies has been shown that NCC patients exhibit a depressed peripheral cellular immune response [38], although this is controversial [39],[40]. In other helminth infections, results indicate that released products may interfere with the generation of pro-inflammatory mediators [41], the antigen presentation process [42] and other immune defense mechanisms elicited by the host upon helminth infection [3],[43],[44].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 ( 120–135) shows the immunologic actors associated with the different clinical or radiological phenotypes of NC. From necropsies come the harder data on the immunological actors involved in the inflammatory process in NC.…”
Section: The Immune Response In Human Neurocysticercosismentioning
confidence: 99%
“…Data are consistent with other observations indicating that innate and adaptive arms of the host-immune response may be downregulated in response to T. solium (42, 44, 50, 51). In contrast, there was no evidence of immune suppression in Con A-stimulated PBMCs from NCC patients compared with controls (52), and active peripheral immunity was reported in NCC patients (53). The effect on plasma TNF-α and CXCL8 concentrations was relatively specific, with no detectable changes in the peripheral concentrations of a broad range of proinflammatory cytokines or their inhibitors in NCC patients.…”
Section: Discussionmentioning
confidence: 89%